Patrimonial atony by COVID-19: in the municipal management of Qoricancha and San Agustin (sg-3) of the Historical Center of Cusco between the years 2020-2021 - Canales Zuniga, Freed (2023)
The present study has been carried out during the current sanitary crisis circumstances due to COVID-19 and its impact during the municipal management between march 15, 2020 and February 29, 2021 in the Historical Center of Cusco SG-3, given that, the development of the pandemic is localized in urban neighborhoods where people live and work, and municipalities have been carrying out public activities to confront the negative impact of the pandemic. The report presents a perspective from heritage "subjects" such as the Provincial Municipality of Cusco and its handling of the sanitary crisis in this sector of Cusco as a heritage site, from the municipal instances that handle management, planning, legislation, financial training and engagement in international and interinstitutional cooperation - we pretend to articulate the situational reality of the PMC as it carries out its responsibility for preserving the city's cultural heritage and citizenship, revealing its real capacity for action in the face of the permanent problems it faces on a daily basis.